2017
DOI: 10.1073/pnas.1706522114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic maps of UV damage formation and repair for the human genome

Abstract: Formation and repair of UV-induced DNA damage in human cells are affected by cellular context. To study factors influencing damage formation and repair genome-wide, we developed a highly sensitive single-nucleotide resolution damage mapping method [high-sensitivity damage sequencing (HS-Damage-seq)]. Damage maps of both cyclobutane pyrimidine dimers (CPDs) and pyrimidine-pyrimidone (6-4) photoproducts [(6-4)PPs] from UV-irradiated cellular and naked DNA revealed that the effect of transcription factor binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
259
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(271 citation statements)
references
References 40 publications
12
259
0
Order By: Relevance
“…T-asymmetry and the difference between genic and non-genic regions are the main results of the Damage-seq experiments 30 that support the utility of the data for the genome-wide analysis of bulky DNA damage and repair by the NER system. Thus, for quality control of the Damage-seq data, we calculated T-asymmetry and the ratio of reads in intergenic and genic regions separately for all replicas.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…T-asymmetry and the difference between genic and non-genic regions are the main results of the Damage-seq experiments 30 that support the utility of the data for the genome-wide analysis of bulky DNA damage and repair by the NER system. Thus, for quality control of the Damage-seq data, we calculated T-asymmetry and the ratio of reads in intergenic and genic regions separately for all replicas.…”
Section: Methodssupporting
confidence: 54%
“…The XR-seq dataset for cyclobutane pyrimidine dimers (CPD) reported in Adar et al 29 allowed us to estimate the amount of DNA damage actively repaired by NER following UV irradiation. To directly assess the presence of unrepaired DNA damage, we used the Damage-seq data for CPDs provided by Hu et al 30 . We did not use XR-seq and Damage-seq data for pyrimidinepyrimidone (6-4) photoproducts because these lesions are repaired too quickly to permit an accurate analysis of the effect of damage bypass over successive rounds of replication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it has been shown that 5mC facilitates CPD formation by UVB (280-315 nm), the main inducer of CPDs in sunlight, but not by UVC (100-280 nm) 25,26 , which does not penetrate the atmosphere. Despite this, genome-wide studies of CPD formation in human cells to date have all been performed using UVC 14,15,27,28 . To address this, we mapped CPDs genome-wide in human A375 melanoma cells immediately following exposure to UVB (310 nm), using a protocol based on T4 endonuclease V digestion and Illumina sequencing as described previously for UVC 15 (Fig.…”
Section: Reduced Pyrimidine Dimer Formation By Uvb In Promoters With mentioning
confidence: 99%
“…23,26,30 While the thymine dimer T^T CPD opposite its canonical adenine (AA) bases in the complementary strand is NER-resistant, it becomes an excellent substrate of NER when these AA bases are replaced by “mismatched” GG. 10 The development of genome-wide methods of analysis of the formation and repair of these UV photolesions in human fibroblasts, 31 human lymphocytes, 32 and yeast 30 genomes has provided novel insights into the base sequence dependence of mutational processes at the single nucleotide level of resolution.…”
Section: Recognition Of Dna Damage and Initiation Of Gg-nermentioning
confidence: 99%